Viruses : biology, applications, control - Harper, D. R. (David R.); Harper, D. R. (David R.). (New York : Garland Science, 2012)
'Viruses: Biology, Applications, and Control is a concise textbook for advanced undergraduate and graduate students and is an updated and expanded version of the Second Edition of David Harper's Molecular Virology. Focusing on key mechanisms and developments, Viruses presents many recent scientific advances, including virus evolution, emerging infections, virus extinction, control of infections, antiviral drugs, gene therapy, bacteriophage therapy, and diagnostics. The first chapters introduce the reader to the structure and nature of viruses, including their classification and evolution. As viruses cause widespread and serious disease, the ensuing chapters explain how they interact with the immune system and the different ways we try to defeat them: vaccines, antiviral drugs, and immunotherapy. Laboratory methods for viral detection and laboratory diagnosis are also covered. While viruses do cause disease, many do not, and their special biology means they can have beneficial uses and this aspect of viruses is included. One of the most interesting areas in virology, given extensive coverage here, is how new viruses emerge and establish themselves. Viruses: Biology, Applications, and Control is a rigorous treatment of the molecular side of virology and its conceptual approach makes it an essential text for students and non-specialists'--Provided by publisher.
Expanded version of Molecular virology / David Harper. 2nd ed. 1998.
Includes bibliographical references and index.
Keywords: Molecular virology; Virus diseases -- Molecular aspects; Viruses; Antiviral agents; Immunity